2013
DOI: 10.1116/1.4843595
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of molybdenum oxide using bis(tert-butylimido)bis(dimethylamido) molybdenum

Abstract: Molybdenum trioxide films have been deposited using thermal atomic layer deposition techniques with bis(tert-butylimido)bis(dimethylamido)molybdenum. Films were deposited at temperatures from 100 to 300 °C using ozone as the oxidant for the process. The Mo precursor was evaluated for thermal stability and volatility using thermogravimetric analysis and static vapor pressure measurements. Film properties were evaluated with ellipsometry, x-ray photoelectron spectroscopy, secondary ion mass spectroscopy, and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 9 publications
1
91
0
1
Order By: Relevance
“…The set temperature of the substrate table was varied between 50 and 350 C. The temperature of the reactor wall was maintained at 100 C, for all depositions, except for depositions at a table temperature of 50 C, for which the wall temperature was set to 50 C. The liquid (N t Bu) 2 (NMe 2 ) 2 Mo precursor (98%, Strem Chemicals) was contained in a bubbler at 50 C, at which it is reported to have a vapor pressure of 0.13 Torr. 21 The chemical structure of the precursor can be seen in the inset of Fig. 1.…”
Section: Experiments a Film Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The set temperature of the substrate table was varied between 50 and 350 C. The temperature of the reactor wall was maintained at 100 C, for all depositions, except for depositions at a table temperature of 50 C, for which the wall temperature was set to 50 C. The liquid (N t Bu) 2 (NMe 2 ) 2 Mo precursor (98%, Strem Chemicals) was contained in a bubbler at 50 C, at which it is reported to have a vapor pressure of 0.13 Torr. 21 The chemical structure of the precursor can be seen in the inset of Fig. 1.…”
Section: Experiments a Film Depositionmentioning
confidence: 99%
“…More recently, Bertuch et al reported an ALD process to deposit MoO x using bis(tert-butylimido)-bis(dimethylamido)-molybdenum, (N t Bu) 2 (NMe 2 ) 2 Mo, as the metal-organic precursor and ozone as reactant. 21 This process promisingly shows a high growth per cycle (GPC) of $1.3 Å at 300 C, but suffers from a low GPC and from C and N contamination in the films at lower deposition temperatures of 150-200 C.…”
Section: Introductionmentioning
confidence: 99%
“…al. [8] ure5). While the 2 second O 2 plasma process shows no sub band gap absorption the additional Argon plasma step leads to small, wide sub band gap absorption in the MoO x layers the.…”
Section: Resultsmentioning
confidence: 99%
“…Although the hole-selective conductivity mechanism through the MoO x /(i)a-Si:H/(n)c-Si stack is not fully understood in detail, it is influenced by the defect state density in the MoO x as well as the MoO x layer thickness itself [3] [4]. For depositing very thin (<10 nm), conformal oxides on structured silicon surfaces atomic layer depostion (ALD) is due to its reaction-limited growth process an ideal candidate [5].Thermal ALD recipes for MoO x are recently reported by different groups, but up to now non of these MoO x layers are tested as emitter alternative in SHJ solar cells [6][7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are two molybdenum precursors reported for MoO 3 : C 12 H 30 N 4 Mo [57] and Mo(CO) 6 [58]. Likewise there were two kind of tungsten precursors used for WO 3 : W(CO) 6 [59][60][61] and W 2 (NMe 2 ) 6 [62].…”
Section: Atomic Layer Depositon (Ald)mentioning
confidence: 99%